Role of Parents in the Academic Development of a Child with ADHD - Burhan, Mulya (Candradimuka: Journal of Education, 2024)
This study aims to discover what motivates children with ADHD (Attention Deficit Hyperactivity Disorder) to perform academically. In addition, this paper also tries to search viable methods to assist children with ADHD and what factors determine their academic motivation. The research method used is descriptive qualitative research method. The primary focus of this study were children with ADHD and their parents or legal guardians. The techniques used in this research included rigorous observation, interrogation, and documentation based on the notion that the academic motivation of students with ADHD tends to be lower than that of students in with no discernable mental disorder. This is mostly due to three prominent symptoms: hyperactivity, inattention, and impulsivity. Symptoms like these effectively renders them less productive, and children with ADHD requires a specialized approach in nurturing and development, like allocating more attention to detail and being able to handle them patiently without applying harsh or punitive measures as it will affect their mental and psychological state.